Elizabeth I and foreign policy, 1558-1603 - Doran, Susan (Lancaster pamphlets., 2000)
Describes and assesses England's foreign policy during the second half of the sixteenth century. It includes coverage of relationships with foreign powers, the effect of the Reformation, war with Spain and Elizabeth as a stateswoman.